DNA AND ANTIMICROBIAL FINGERPRINTING OF MEDICINAL ALOE SPECIES FROM THE MASCARENE ISLANDS - Govinden-Soulange, J.; Khoyratty, S.; Ranghoo-Sanmukhiya, M.; Makunga, N.; Kodja, H. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Antimicrobial and molecular studies of three endemic medicinal plants from Mauritius L. tomentorii and L. purpureum and Lomatophyllum macrum from Reunion Island was carried out to differentiate them from Aloe vera which belongs to the same family Asphodelaceae. These endemic Aloes are used in the Mauritian and Reunion pharmacopoeia to treat bacterial infections and as antispasmodic.3 Phytochemical screening of the crude extracts revealed the common presence of alkaloids, anthraquinones, coumarins, phenols, saponins and tannins. Anthraquinones and saponins had also been reported as bioactive compounds present in Alooideae and in Aloe vera 1,4 .Antimicrobial activity was tested against Escherichia coli, Klebsiella pneumoniae and Staphylococcus aureus using the microplate dilution method. Extracts of Lomatophyllum species showed more potent antimicrobial activity than Aloe vera with MIC ranging 0.003-0.006mg/L as compared to 0.012-.0.028mg/L for Aloe vera .The antimicrobial properties of L. tormentorii and L. purpureum were attributed to the presence of alkaloids, coumarins, and saponins which are known to possess antimicrobial attributes. In this study we also used a modified RAPD-PCR technique. to elucidate the genetic closeness of Lomatophyllum to Aloe. Genomic DNA was extracted using a modification of the method used by Govinden-Soulange et al (2007)2. RAPD-PCR technique has revealed that Lomatophyllum species and Aloe vera share some genetic similarities. Consequently we report the genetic diversity of the Lomatophyllum species by measuring the genetic distance, which they have with Aloe vera. Moreover some biologically active compounds within the Lomatophyllum were identified and their possible similarities with Aloe vera were unveiled. Key Words: Biological activities, Lomatophyllum, Aloes, genetic distanceReferences: 5. Atherton, P. (1999). Aloe vera: myth or medicine? Positive Health, 20 June/July.6. Govinden-Soulange J, Ranghoo-Sanmukhiya M, Seeburrun SD. (2007). Tissue culture and RAPD analysis of Cinnamomum camphora and Cinnamomum verum. Biotechnology. 6(2):239-2447. Gurib-Fakim, A. Gueho, J., Sewraj, M. and Dulloo, E. (1994). Plantes Medicinales de l’Ile Rodrigues. Editions de l’Ocean Indien, Maurice.8. Mark, W.C., Anette, Y.D., Anthony, V.C., Gail, R., Paula, J.R. Margaret, A.T. and Lui, E.E. (2000). Phylogenetics of Asphodelaceae (Asparagales): Analysis of Plastid rbcL and trn-L-F DNA Sequences. Annals of Botany, 86: 935-951.